NARRATIVE REVIEW: TEETH WHITENING FOR DIFFERENT DISCOLOURATION CHALLENGES - YUSOF, HAZIRA M (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Nowadays, there are countless latest comprehensive studies done on the subject of tooth whitening for different discolouration challenges available coming out each year. The objective of this study is to provide an insight and guide to different tooth whitening modalities, their indications and potential side effects to ensure optimum treatment planning. The Scale for the Assessment of Narrative Review Articles (SANRA) is used as a guide for the articles chosen. Articles were searched in PubMed/Medline to identify relevant articles using the combination of search terms: teeth whitening, whitening toothpaste, tooth discolouration with a combination of each discolouration challenge. The literature retrieved was then narrowed down only for teeth whitening that corresponds to causative factors and the repeated and similar types of treatment were eliminated. A comprehensive literature search was conducted on PubMed and Scopus databases. A separate search was made on a Google search engine. The references from the reviewed material were used to locate other relevant publications. Different discolouration challenges will affect the final outcome of the treatment. It is vital for dentists to have knowledge of tooth whitening modalities available and their specific indications and limitations. Tooth whitening procedures are a minimally invasive way to improve dental aesthetic, conservatively.